1999
DOI: 10.1038/sj.sc.3100839
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic syringomyelia

Abstract: Post-traumatic syringomyelia is estimated to develop in more than 20% of individuals with traumatic spinal cord injury (SCI). The development can give rise to clinical symptoms 6 months to 26 years after the injury, and presentation 40 years post-injury has been seen by one of the authors. 1 ± 4 We present an unusual case for comments and discussion.Keywords: spinal cord injury; post-traumatic syringomyelia; tetraplegia; progressive symptoms Case storyA forty-year-old man was involved in an accident as a pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
2
1
Order By: Relevance
“…Neurological deterioration was found in 14% of the patients in both the countries. This figure is o20%, the estimation in the article by Nielsen et al 14 This may have to do with the fact that our duration of injury was somewhat less than in the Nielsen study. Nielsen et al showed that syringomyelia can give rise to symptoms 26 years after injury.…”
Section: Discussioncontrasting
confidence: 41%
“…Neurological deterioration was found in 14% of the patients in both the countries. This figure is o20%, the estimation in the article by Nielsen et al 14 This may have to do with the fact that our duration of injury was somewhat less than in the Nielsen study. Nielsen et al showed that syringomyelia can give rise to symptoms 26 years after injury.…”
Section: Discussioncontrasting
confidence: 41%
“…19,39,47,66 However, not all types of pain respond equally to successful treatment of posttraumatic syringomyelia. Pain provoked by maneuvers such as coughing or sneezing usually improves if the syrinx regresses postoperatively.…”
Section: Short-term Outcomementioning
confidence: 99%
“…The development of post-traumatic syringomyelia is a well-known example where even extensive changes in spinal cord morphology are detected, either by chance (routine MRI scans) or due to the development of rather minor and less specific symptoms (like increasing pain and spasticity) (Figure 3). [43][44][45][46] The common denominator is that these disorders and related changes occur very slowly. This provides evidence that the cord is capable of tremendous plastic changes over a relatively long time.…”
Section: Translation Of Outcome Measuresmentioning
confidence: 99%